Finite element analysis of car hood model for impact test by using solidworks software in automotive application - Nur Zulaika Mohd Jamani (2017)
Automotive industry is the fastest growing industry today. In the competitive business the automobile companies have to take care of the cost of vehicle, its efficiency and service. In addition, mostly a front position of the vehicle gets damaged including car hood. So, there is need of optimization of existing design of car hood. Design and materials of engine hood has been a key point for an automotive industry due to lightweight, high specific stiffness and strength. In another study on engine hood material, a composite, aluminium and steel were compared using numerical analysis software. In this study, a model of car hood was created by using SolidWorks Software and the study also describe the impact test on car hood using finite element analysis. This study is to predict the best material used for car hood application resulted from their maximum stress and displacement after impact test. The type of materials used, and the effect of forces to the stress and displacement of car hood model were investigated and discussed. The results indicated that the finite element analysis modelling of Carbon Fibre Reinforced Plastic-Foam Sandwich composite can effectively predict the deformation of the car hood and it was the best material that should be used in car hood application.